The primitive Christian attitude to the state as reflected in the New Testament writings - Hopton, George Irvine (The University of Edinburgh, 1967)
This thesis finds Jesus' attitude to the state normative for the whole period of the New Testament writings* The most important state for him was not Rome but the Jewish theocracy. He was greatly concerned that the latter entity would see its political responsibility in terms of the prophetic image of the suffering servant.

The development of Israel as a state is traced, as is the vision of the future ideal state which, described in frankly political terms, motivated the Jews to seek recovery of independence and power, an era of peace and prosperity, of fidelity to God and his law, and of Justice and brotherly love among men

The period leading up to New Testament times is seen as an era of crisis for the Jewish nation. External forces threaten its cohesion. Some of its citizens want to compromise with intrusive foreign cultures} some want to retreat to a piestic enclave; some counsel rebellion. Jesus' answer to the crisis was in the prophetic tradition. It was to challenge the preconceptions of political morality which lay behind each of the options, and to ask men to consider themselves citizens of a kingdom whose ethic is love. In fulfilling their duty to the higher righteousness they would be good citizens of present states and exert tension on the present systems which could lead to their transformation.

All the books of the Hew Testament are dealt with in the chronological order of their composition. In deciding what evidence is applicable to the subject, several themes which relate to the attitude t o the state are kept in mind.

Order is Judged to be one such category. The existence of man in society is possible only when chaos is overcome by unity and order. Yet the goal of order is continually threatened by external invasions and by the attempt to introduce heightened ethical demands into society.

Sschatology is another important subject because, depending on the type of eschatology which was stressed in a particular writing, we may ascertain a particular attitude to history. In some cases history is taken seriously as the normal realm of a Christian's activity. In others a non-dynamic view of history is adopted with its resultant lack of responsibility for the state.

Passages dealing with universalism are also important reference points for this subject. Each person's basic political philosophy arises out of his attitude to the particular entity to which he is attached* There was a prophetic attempt to expand this consciousness toward a universal outlook in Hew Testament times.

Attitudes under persecution and the theme of national identity are also dealt with fully, as is the dominant New Testament theme of suffering love. Jesus had been a loving, suffering servant within the life of his own nation. The early church understood its responsibility to society in terms of being a salty presence within history, of seeing that the kingdom ethic exerted a judging, transforming tension upon the ethic of measurable duty by which the states of the present world live.